Retail instalment credit : growth and legislation - McAlister, Edgar Ray. (Columbus, Bureau of Business Research, Division of Research, College of Commerce and Administration, Ohio State University, 1964)
This book described consumer credit as an integral part of the present-day American economy. At the point of purchase for final consumption by house-hold consumers, as at other points in the process of production and distribution, credit is indispensable to high-volume operation.
includes tables
Bibliography: p. [193]-197.
II 18/01/2019
Loans
Keywords: Conditional sales; Conditional sales; Installment plan